Shock Wave Therapy Alleviates Hypoxia/Reoxygenation-Induced Cardiomyocyte Injury by Inhibiting Both Apoptosis and Ferroptosis - Jiannan Wang; Na Jia; Kaiyi Zhu; Kun Xu; Mingjing Yan; Ming Lan; Junmeng Liu; Bing Liu; Tao Shen; Qing He (Analytical Cellular Pathology)
Shock wave therapy (SWT) is a new alternative therapy for patients with severe coronary artery disease that improves myocardial ischemic symptoms by delivering low-energy shock wave stimulation to ischaemic myocardium with low-energy pulsed waves. However, the specific mechanism of its protective effect is not fully understood, especially for the protective mechanism in cardiomyocytes after hypoxia/reoxygenation (H/R). We selected a rat H9c2 cardiomyocyte cell line to establish a stable H/R cardiomyocyte injury model by hypoxia/reoxygenation, and then used SWT for therapeutic intervention to explore its cardiomyocyte protective mechanisms. The results showed that SWT significantly increased cell viability and GSH levels while decreasing LDH levels, ROS levels, and MDA levels. SWT also improved mitochondrial morphology and function of cells after H/R. Meanwhile, we found that SWT could increase the expression of GPX4, xCT, and Bcl-2, while decreasing the expression of Bax and cleaved caspase-3, and inhibiting cardiomyocyte apoptosis and ferroptosis. Moreover, this protective effect of SWT on cardiomyocytes could be significantly reversed by knockdown of xCT, a key regulator protein of ferroptosis. In conclusion, our study shows that SWT can attenuate hypoxia–reoxygenation-induced myocardial injury and protect cardiomyocyte function by inhibiting H/R-induced apoptosis and ferroptosis, and this therapy may have important applications in the treatment of clinical myocardial ischemic diseases.